Seasonal variations in physical fitness and performance indices of elite soccer players - Meckel, Y.; Doron, O.; Eliakim, E.; Eliakim, A. (Sports, 2018)
The aim of the study was to investigate seasonal variations in fitness and performance indices of professional male soccer players. Eighteen professional male soccer players (age range 22-32 years) completed three similar sets of tests at three stages of the season: before preseason; after preseason and the middle of the competitive in-season. A significant decrease in body mass and percent fat was found during the preseason. A significant improvement (p < 0.05) was found in the vertical jump (preseason: 37.0 ± 5.3, post-preseason: 39.0 ± 4.8, mid-season: 40.3 ± 5.5 cm), the 4 × 10-m agility test (preseason: 8.1 ± 0.2, post-preseason: 7.9 ± 0.2, mid-season: 8.1 ± 0.3 s), flexibility (preseason: 45.2 ± 8.8, post-preseason: 48.2 ± 7.0, mid-season: 49.9 ± 6.9 cm) and aerobic capacity (preseason: 52.7 ± 6.6, post-preseason: 56.4 ± 6.0, mid-season: 57.4 ± 5.4 mL/kg/min) during preseason, with no further change during mid-season. Repeated sprint test (RST) (6 × 30-m) performance indices showed significant deterioration (p < 0.05) in ideal sprint time (IS; preseason: 21.8 ± 1.0, post-preseason: 23.0 ± 0.8, mid-season: 23.2 ± 0.8 s) and total sprint time (TS; preseason: 22.5 ± 0.7, post-preseason: 23.5 ± 0.6, mid-season: 23.8 ± 0.6 s) during preseason, with no further changes during mid-season. However, performance decrement (PD) significantly decreased during the preseason with no change during mid-season. The findings suggest that while power training was probably responsible for the anaerobic fitness improvement, the high-volume training led to improvement in aerobic fitness during the preseason. However, the low-intensity aerobic-type training, coupled with the high total training load, may have led to fatigue and decreases in IS and TS during the preseason